Game-based e-learning applications of e-tester - Dreher, Heinz; Williams, Robert; Guetl, C.; Maurer, H. (Association for the Advancement of Computing in Education, 2005)
Adaptive E-Learning systems may be a supportive solution for a wide range of learning applications. In order to complement common learning paradigms in computer-based education the digital game-based learning paradigm is an interesting alternative, through which we can increase motivation, intrigue learners for a new or a previously boring subject, and provide another, more relaxing environment for self-assessment and testing. Despite of these advantages, one main shortcoming is that the creation of game stories and curriculum-relevant game content is an enormous workload for teachers and learning content providers. In order to reduce the learning game creation effort, we propose an enhanced digital game-based learning approach by applying a flexible game shell in combination with auto-generated questions based on the course content and automatic assessment of natural language answers. On the basis of requirements within the AdeLE research project and application scenarios, our development approach as well as the first prototype implementation are highlighted. First experiences and tests based on the prototype implementation are promising.